2008
DOI: 10.1099/jmm.0.47634-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping analysis of Mycoplasma pneumoniae clinical strains in Japan between 1995 and 2005: type shift phenomenon of M. pneumoniae clinical strains

Abstract: Mycoplasma pneumoniae clinical isolates obtained between 1995 and 2005 were examined to determine the prevalent genotype. One hundred and twenty-seven strains isolated from bronchitis and pneumonia patients were genotyped by a PCR-RFLP method based on nucleotide sequence polymorphisms of the p1 gene, which encodes the major adhesin protein. The typing results established that 66 of the isolates were group I strains, 45 were group II strains and 16 were group II variants. Analysis of the annual occurrence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
114
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 25 publications
11
114
3
3
Order By: Relevance
“…The existence of these two types of the P1 gene (type 1 and type 2) was shown to be an excellent marker for numerous other variations within their genomes, some of which likely lead to virulence differences observed among strains (8). It is possible that well-documented shifts of clinical M. pneumoniae isolates in different locations over time could be a result of type-associated differences (23). One hypothesis speculates that type-specific antibodies render protection against the causative type strain, leading to replacement by the other strain type.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of these two types of the P1 gene (type 1 and type 2) was shown to be an excellent marker for numerous other variations within their genomes, some of which likely lead to virulence differences observed among strains (8). It is possible that well-documented shifts of clinical M. pneumoniae isolates in different locations over time could be a result of type-associated differences (23). One hypothesis speculates that type-specific antibodies render protection against the causative type strain, leading to replacement by the other strain type.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in recent years, three variants of M. pneumoniae showing sequence variations in one of these two repetitive elements were described (4, 6, 11). Variant 2a strains were reported with increasing numbers in Japan (12) and Europe (6), but only one isolate has been characterized as variant 1. Variant 2b isolates were detected in limited number with a molecular subtyping method in Europe only (6); therefore, DNA samples from cultures of this genotype could not be included in the present study.…”
mentioning
confidence: 99%
“…Sixty of 201 M. pneumoniae clinical isolates were genotyped by full-length sequencing of the p1 gene in our previous report (8); the other 141 isolates were genotyped by a previously reported method (15,16). Results indicated that 184 (91.5%) isolates were type 1, 2 (1.0%) isolates were variant 2a, 15 (7.5%) isolates were variant 2c, and no type 2 isolates were detected.…”
mentioning
confidence: 99%